Interactions between Bifidobacterium and Bacteroides and human milk oligosaccharides and their associations with infant cognition - Cho, Seoyoon; Samuel, Tinu M.; Li, Tengfei; Howell, Brittany R.; Baluyot, Kristine; Hazlett, Heather C.; Elison, Jed T.; Zhu, Hongtu; Hauser, Jonas; Sprenger, Norbert; Lin, Weili (Frontiers in Nutrition, 2023)
While ample research on independent associations between infant cognition and gut microbiota composition and human milk (HM) oligosaccharides (HMOs) has been reported, studies on how the interactions between gut microbiota and HMOs may yield associations with cognitive development in infancy are lacking. We aimed to determine how HMOs and species of Bacteroides and Bifidobacterium genera interact with each other and their associations with cognitive development in typically developing infants. A total of 105 mother-infant dyads were included in this study. The enrolled infants (2.9-12 months old (8.09±2.48)) were at least predominantly breastfed at 4 months old. A total of 170 HM samples from the mothers and fecal samples of the children were collected longitudinally. Using the Mullen Scales of Early Learning to assess cognition and the scores as the outcomes, linear mixed effects models including both the levels of eight HMOs and relative abundance of Bacteroides and Bifidobacterium species as main associations and their interactions were employed with adjusting covariates; infant sex, delivery mode, maternal education, site and batch effects of